Enhancement of the Anti-Inflammatory Activity of NSAIDs by Their Conjugation with 3,4,5-Trimethoxybenzyl Alcohol - Tziona, Paraskevi; Theodosis-Nobelos, Panagiotis; Papagiouvannis, Georgios; Petrou, Anthi; Drouza, Chryssoula; Rekka, Eleni A (My University, 2022)
The synthesis of derivatives of three nonspecific COX-1 and COX-2 inhibitors, ibuprofen, ketoprofen, naproxen is presented. These acids were connected via an amide bond with an amino acid (L-proline, L-tyrosine, and beta-alanine) used as a linker. The amino acid carboxylic group was esterified with 3,4,5 trimethoxybenzyl alcohol. The activity of the novel derivatives was examined in vivo on carrageenan-induced inflammation, and in vitro, as cyclooxygenase and lipoxygenase inhibitors. It was found that the new compounds were more potent anti-inflammatory agents than the parent drugs. Thus, the ibuprofen (21) and ketoprofen (16) derivatives reduced rat paw edema by 67 and 91% (the reduction by the relevant NSAIDs was 36 and 47%, respectively). They inhibited COX-2 more than the starting drugs (21 by 67%, ibuprofen 46%, 19 by 94%, ketoprofen 49%). Docking of compounds on the active sites of COX-1 and COX-2 reflects their in vitro activity. Thus, 19 adopts an unfavorable orientation for COX-1 inhibition, but it binds effectively in the binding pocket of COX-2, in agreement with the absence of activity for COX-1 and the high inhibition of COX-2. In conclusion, the performed structural modifications result in the enhancement of the anti-inflammatory activity, compared with the parent NSAIDs.
Keywords: anti-inflammatory derivatives; cyclooxygenase inhibition; lipoxygenase inhibition; molecular docking; non steroidal anti-inflammatory drugs